sBotics: Simulation Applied for the Practical Component of the Brazilian Robotics Olympiad - Nascimento, Lucas; Neri, Davi; Nascimento, Thiago; Yamaguibashi, Erika; Sá, Sarah; Gonçalves, Luiz (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
The idea that will be presented in this paper endeavours the use of a web robotics simulation platform throughout Brazil, particularly the simulation of the first two categories of its national robotics competition, the Brazilian Robotics Olympiad (OBR). On this tournament, contestants use robotic kits (such as LEGO's EV3 and Arduino-based kits) to simulate the rescue of a victim in a disastrous situation. The idea of this project is to offer an alternative for those who seek to test their knowledge through other means not needing physical resources, or does not have access to robotic kits normally used by participants in robotics tournaments, a problem predominant in Brazil's diverse and unequal society.